Percutaneous Image-Guided Ablation of Breast Tumors: An Overview - Sag, Alan A.; Maybody, Majid; Comstock, Christopher; Solomon, Stephen B. (Seminars in Interventional Radiology, 2014)
Percutaneous non-surgical image-guided ablation is emerging as an adjunct or alternative to surgery in the management of benign and malignant breast tumors. This review covers the current state of the literature regarding percutaneous image-guided ablation modalities, clinical factors regarding patient selection, and future directions for research.
Keywords: percutaneous ablation; breast cancer; fibroadenoma; immunomodulation; interventional radiology